Segunda contribución al conocimiento de la estructura taxonómica del género Liolaemus Wiegmann (Iguanidae) - Laurent, Raymond F. (1985)
The author shows that several groups of species can be distinguished in the genus or supergenus Liolaemus Wiegmann, outside the subgenus Ortholaemus already recognized (Laurent, 1983a). The typical subgenus Liolaemus sensu stricto includes most Chilean species a few Argentinian and some Bolivian and Peruvian forms. An Argentinian group which includes most Argentinian, Bolivian and Peruvian species (several undescribed), can be named Eulaemus Girard, 1854. A Patagonian primitive group includes L. kingi, L. archiforus and L. ruizleali; its name could be Rhytidodeira Girard, 1957. The genus Vilcunia Donoso-Barrios and Cei can be considered another subgenus comprising, besides V. silvanae and V. periglacialis, L. lineomaculatus Boulenger. Lastly the southermost species, L. magellanicus, constitutes by itself a monotypical group related to Vilcunia.